Pi sensing and signalling: from prokaryotic to eukaryotic cells. (9th June 2016) - Qi, Wanjun; Baldwin, Stephen A.; Muench, Stephen P.; Baker, Alison
Abstract : Phosphorus is one of the most important macronutrients and is indispensable for all organisms as a critical structural component as well as participating in intracellular signalling and energy metabolism. Sensing and signalling of phosphate (Pi ) has been extensively studied and is well understood in single-cellular organisms like bacteria ( Escherichia coli ) and Saccharomyces cerevisiae . In comparison, the mechanism of Pi regulation in plants is less well understood despite recent advances in this area. In most soils the available Pi limits crop yield, therefore a clearer understanding of the molecular basis underlying Pi sensing and signalling is of great importance for the development of plants with improved Pi use efficiency. This mini-review compares some of the main Pi regulation pathways in prokaryotic and eukaryotic cells and identifies similarities and differences among different organisms, as well as providing some insight into future research.